2015
DOI: 10.1093/imammb/dqv028
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of an equatorial cerclage on closure of posterior retinal detachment

Abstract: A mechanics-based mathematical model of an eye possessing a posterior retinal detachment is presented for the case where an encircling scleral buckle (a cerclage) is sutured around the equator of the eye. The mechanical behaviour of the retina and the globe, both before and after applying the cerclage, is studied. An energy formulation yields the self-consistent equations of equilibrium and boundary conditions of the ocular system, and analytical solutions are established for the scleral buckle, for the globe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The influence of a cerclage over posterior retinal detachments have been investigated with experimental mechanical models by Ge et al, who recently demonstrated that equatorial buckling has a marked influence on neurosensory reattachment posterior to the equator, in accordance with our findings. 26 The SB standardized approach hereby discussed implies the execution of a pneumatic retinopexy plus SRF drainage in almost all cases, except for shallow RRDs in which air injection may be avoided. SRF drainage allows the retina to flatten before the scleral fixation of the buckle.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of a cerclage over posterior retinal detachments have been investigated with experimental mechanical models by Ge et al, who recently demonstrated that equatorial buckling has a marked influence on neurosensory reattachment posterior to the equator, in accordance with our findings. 26 The SB standardized approach hereby discussed implies the execution of a pneumatic retinopexy plus SRF drainage in almost all cases, except for shallow RRDs in which air injection may be avoided. SRF drainage allows the retina to flatten before the scleral fixation of the buckle.…”
Section: Discussionmentioning
confidence: 99%